English Teachers’ Perception in Implementing Merdeka Curriculum At Senior High School - Asti Suloso, Luluk Wiji (Jurnal Dimamu, 2024)
This research aims to find out and describe what is English teachers' perception in implementing Merdeka Curriculum at SMAN 1 Rancaekek, what are the problems faced by English teachers in implementing Merdeka Curriculum at SMAN 1 Rancaekek, and what are the teachers' strategies for overcoming problems faced in implementing Merdeka Curriculum at SMAN 1 Rancaekek.  This research was conducted at SMAN 1 Rancaekek and used qualitative descriptive methods. Data collection was carried out through questionnaires, interviews, and document analysis. The participants in this research were four English teachers. The data results from the questionnaire are divided into 5 indicators; launch of Merdeka Curriculum, Merdeka Curriculum priority stage, design principles and implementation mechanism of Merdeka Curriculum, direction of change in Merdeka Curriculum, and structure and framework of Merdeka Curriculum.  The results of the study show that teachers have a positive perception of the implementation of the Merdeka Curriculum at SMAN 1 Rancaekek. However, in its implementation, English teachers face several problems such as designing lesson plans, students with low learning motivation, and limitations of Merdeka Curriculum-based textbooks as learning resources. To overcome this problem, English teachers use several strategies, such as adjusting in preparing teaching modules, participating in the English Subject Teacher Deliberation (MGMP) forum, and increasing students' learning motivation in learning English. Therefore, even though English teachers have positive perceptions, they still need adaptation in their implementation.